Single and two-dose typhoid conjugate vaccine safety and immunogenicity in HIV-exposed uninfected and HIV-unexposed uninfected Malawian children - Nginache Nampota-Nkomba; Osward M. Nyirenda; Victoria Mapemba; Rhoda Masonga; Priyanka D. Patel; Theresa Misiri; Felistas Mwakiseghile; Richard Wachepa; John M. Ndaferankhande; Bright Lipenga; Pratiksha Patel; Happy Banda; et al. (Taylor & Francis Group, 2024)
Vaccine safety and immunogenicity data in human immunodeficiency virus (HIV)-exposed uninfected (HEU) children are important for decision-making in HIV and typhoid co-endemic countries. In an open-label study, we recruited Malawian HEU and HIV unexposed uninfected (HUU) infants aged 9 - 11 months. HEU participants were randomized to receive Vi-tetanus toxoid conjugate vaccine (Vi-TT) at 9 months, Vi-TT at 15 months, or Vi-TT at 9 and 15 months. HUU participants received Vi-TT at 9 and 15 months. Safety outcomes included solicited and unsolicited adverse events (AE) and serious AEs (SAEs) within 7 days, 28 days, and 6 months of vaccination, respectively. Serum was collected before and at day 28 after each vaccination to measure anti-Vi IgG antibodies by enzyme-linked immunosorbent assay (ELISA). Cohort 1 (66 participants) enrollment began 02 December 2019, and follow-up was terminated before completion due to the COVID-19 pandemic. Cohort 2 (100 participants) enrollment began 25 March 2020. Solicited AEs were mostly mild, with no significant differences between HEU and HUU participants or one- and two-dose groups. All six SAEs were unrelated to vaccination. Anti-Vi geometric mean titers (GMT) increased significantly from 4.1 to 4.6 ELISA units (EU)/mL at baseline to 2572.0 - 4117.6 EU/mL on day 28 post-vaccination, and similarly between HEU and HUU participants for both one- and two-dose schedules. All participants seroconverted (>4-fold increase in GMT) by the final study visit. Our findings of comparable safety and immunogenicity of Vi-TT in HUU and HEU children support country introductions with single-dose Vi-TT in HIV-endemic countries.